2011
DOI: 10.1158/1940-6207.capr-10-0143
|View full text |Cite
|
Sign up to set email alerts
|

Altered Folate Availability Modifies the Molecular Environment of the Human Colorectum: Implications for Colorectal Carcinogenesis

Abstract: Low folate status increases colorectal cancer risk. Paradoxically, overly abundant folate supplementation, which is not uncommon in the United States, may increase risk. The mechanisms of these effects are unknown. We conducted two translational studies to define molecular pathways in the human colon altered either by folate supplementation or by dietary folate depletion (followed by repletion). In the first study, 10 healthy, at-risk volunteers (with documented stable/normal folate intake) received supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
53
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 35 publications
10
53
1
Order By: Relevance
“…Regional or colon-wide hypomethylation has been reported in the macroscopically normal mucosa of colorectal cancer patients (19,38), raising the possibility of a "field defect" that may predispose to tumor development. In contrast, others have found no significant difference in global (39) or repeat element methylation (40) in this setting, although folic acid supplementation or short-term depletion (sufficient to modify total colonic folate concentration) do not alter colonic global (26) or LINE-1 methylation (41). By analyzing mucosa from large numbers of colorectal cancer and healthy individuals using gold standard assays, this study has definitively showed that the normal mucosa of colorectal cancer patients is no more demethylated than mucosa from endoscopy-confirmed healthy individuals.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Regional or colon-wide hypomethylation has been reported in the macroscopically normal mucosa of colorectal cancer patients (19,38), raising the possibility of a "field defect" that may predispose to tumor development. In contrast, others have found no significant difference in global (39) or repeat element methylation (40) in this setting, although folic acid supplementation or short-term depletion (sufficient to modify total colonic folate concentration) do not alter colonic global (26) or LINE-1 methylation (41). By analyzing mucosa from large numbers of colorectal cancer and healthy individuals using gold standard assays, this study has definitively showed that the normal mucosa of colorectal cancer patients is no more demethylated than mucosa from endoscopy-confirmed healthy individuals.…”
Section: Discussionmentioning
confidence: 59%
“…Most folic acid supplementation trials have not found an increase in colonic mucosa DNA methylation following supplementation (reviewed in ref. 9), although only one of these studies confirmed that folic acid supplementation actually increased colonic folate concentration (26). In a prospective cohort study, Schernhammer and colleagues showed that tumoral LINE-1 hypomethylation was more common in colorectal cancers from individuals with a low dietary folate intake (10).…”
Section: Introductionmentioning
confidence: 99%
“…High intake of folic acid, but not naturally occurring folate, can result in detectable levels of unmetabolized folic acid in serum (55), which in one study was associated with a reduction in the number of cancer-protective natural killer cells (56). Another study found both repletion and supplementation with folic acid (1 mg/d) was associated with upregulation of proinflammatory gene pathways in colorectal tissue (57). Thus, concerns of adverse 1 Cox proportional hazards models adjusted for sex, smoking, physical activity, use of aspirin/nonsteroidal antiinflammatory drugs, BMI, and quintiles of dietary calcium and red meat intakes.…”
Section: Discussionmentioning
confidence: 99%
“…Flexible sigmoidoscopies were performed after a 60-mL tap water enema between 0800 and 1000. Rectosigmoid mucosal biopsy specimens were taken w15 cm from the anal verge as described previously (15,16). Six biopsy specimens for gene expression analysis were taken, immediately frozen in liquid nitrogen, and stored at 2808C.…”
Section: Procedures and Sample Collectionsmentioning
confidence: 99%
“…Our group has completed several studies of molecular events in rectosigmoid mucosal biopsy specimens that accompany administration of putative risk reduction agents such as estrogen and folic acid (15,16). The present study aimed to identify the effects of calcium and/or 1,25-dihydroxyvitamin D 3 [1,25 (OH) 2 D 3 ] supplementation on gene expression profiles of the human colorectal mucosa of subjects at moderate risk of CRC consuming a Western-style diet (WD).…”
Section: Introductionmentioning
confidence: 99%